ADOPTION AND USE OF ‘SYMBICARE’ APPLICATION AMONGST STUDENTS AT AN INDIAN UNIVERSITY - Preetha Menon. Dr. Rajiv Yeravdekar. Dr. Alaka Chandak (International Journal of Modern Agriculture, 2020)
Mobile applications are gaining popularity amongst university students for their health and academic needs. The purpose of this study is to examine the ‘SymbiCare’ app from the lens of its primary stakeholder – the student users. Through in-depth interviews using semi structured questionnaire, this study interviewed 55 graduate students from a large Indian university. Content analysis was conducted on the qualitative data collected from these interviews. Findings from the study can broadly be classified into three main categories – content and information, interface and design and features and utilities. The findings of this study can be used as input to improving the adoption and use of ‘SymbiCare’ app. Thus the app can be turned as an initiative for the students by the students themselves.